Die professionelle Entwicklung von Lehramtsstudierenden mit Unterrichtsfach Religion: Befunde, Interpretationen und Implikationen - Ubani, Martin (Zeitschrift für Pädagogik und Theologie, 2016)
This article discusses some issues related to the professional development of Religious Education (RE) student teachers in initial teacher education based on empirical results on the development of the pedagogical thinking of Finnish RE student teachers during their teacher education. The article begins by describing the concept of professionalism as professional competence, professional identity and professional qualification. After this it describes some key results of the research project related to the first two aspects of professionalism presented earlier. The article closes with some implications for RE teacher education and research on the basis of what was uncovered.